Nutritional profile of Supplemental Nutrition Assistance Program household food and beverage purchases(1)(2) - Grummon, Anna H (Am J Clin Nutr, 2017)
Background: The Supplemental Nutrition Assistance Program (SNAP), which is the largest federal nutrition assistance program in the United States, serves nearly 1 of 7 Americans. To date, few studies have examined food and beverage purchase behaviors in SNAP participants with the use of electronic purchase data. Objective: In this cross-sectional study, we examined household store purchases of key food, beverage, and nutrient groups in SNAP participants and nonparticipants. Design: Using a data set of US households’ (n = 98,256 household-by-quarter observations) packaged food and beverage purchases and SNAP status [current participant, income-eligible nonparticipant (income ≤130% of the Federal Poverty Level [FPL]), and higher-income nonparticipants (income >130% of the FPL)] from 3 quarters during 2012–2013, we estimated pooled ordinary least-squares models, clustered at the household level, to examine the association between SNAP status and purchases while controlling for sociodemographic characteristics. We examined purchases of health- and policy-relevant food and beverage groups [e.g., fruit and sugar-sweetened beverages (SSBs)] and nutrients (e.g., total calories and sodium). Results: Regardless of SNAP status, households had low mean purchases of fruit, vegetables, and fiber and high mean purchases of junk foods, saturated fat, and sodium. After adjustment for multiple comparisons and demographic characteristics, we found significant differences by SNAP status of purchases of fruit, processed meat, salty snacks, sweeteners and toppings, SSBs, and total calories, fiber, sugar, and sodium. Several of these differences were clinically important. For example, compared with income-eligible and higher-income nonparticipants, SNAP participants purchased an additional ∼15–20 kcal · person(−1) · d(−1) from SSBs (P < 0.0001) and ∼174–195 mg total Na · person(−1) · d(−1) (P <0.0001). Results were robust to corrections for sample-selection bias and to the exclusion of observations with potentially misreported SNAP status. Conclusions: American households, including SNAP households, show room for improvement in the nutritional quality of store purchases. New interventions and policies may be needed to improve food and beverage purchases in both SNAP and non-SNAP households.